2019
DOI: 10.15452/cejnm.2019.10.0003
|View full text |Cite
|
Sign up to set email alerts
|

Exploring factors among healthcare professionals that inhibit effective pain management in cancer patients

Abstract: Aim: The aim of this study was to investigate differences in the barriers to good cancer pain management between physicians, nurses, and pharmacists in Jordan. Design: A descriptive correlational design was used to answer the research questions of this study. Methods: A group of 473 participants completed the study questionnaires (Barriers Questionnaire -II and Nurses' Knowledge and Attitudes Survey). Results: Fears related to analgesic use, fears related to opioid side effects, communication, cultural beliefs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 29 publications
2
12
0
1
Order By: Relevance
“…Overall, the results of this review have found some evidence that there are negative attitudes and lack of knowledge towards CPM among the four groups included in this review. These findings are consistent with those of recent studies and systematic reviews [12,13,20,26,37,79,80,96]. Thus, it can be argued that due to these negative attitudes and lack of knowledge towards CPM, the management of cancer pain remains a major problem worldwide, especially in countries within Europe, Africa and Asia [13,26,52,75,76,81,92].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Overall, the results of this review have found some evidence that there are negative attitudes and lack of knowledge towards CPM among the four groups included in this review. These findings are consistent with those of recent studies and systematic reviews [12,13,20,26,37,79,80,96]. Thus, it can be argued that due to these negative attitudes and lack of knowledge towards CPM, the management of cancer pain remains a major problem worldwide, especially in countries within Europe, Africa and Asia [13,26,52,75,76,81,92].…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, understanding patients' culture and beliefs can provide the professional with a consideration into how cancer is viewed by the patient [88]. However, professionals can also be influenced by their culture, as it has been reported that cultural beliefs among professionals were one of the most obviously identified barriers towards CPM [80].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5) However, diverse factors such as fears related to opioid side effects, communication issues, cultural beliefs, and lack of knowledge limit effective pain management. 6) Pain-free hospital initiatives that integrate pain treatment into routine hospital care have been implemented internationally to achieve pain management quality indicators. For example, in Poland, hospitals that maintain high standards of postoperative analgesia in terms of preoperative patient information, assessment and documentation, and monitoring of medication side effects and complications are certified as 'pain-free hospitals' .…”
Section: Introductionmentioning
confidence: 99%